2021
DOI: 10.3389/fcell.2021.697578
|View full text |Cite
|
Sign up to set email alerts
|

Hypothesis and Theory: Characterizing Abnormalities of Energy Metabolism Using a Cellular Platform as a Personalized Medicine Approach for Alzheimer’s Disease

Abstract: Sporadic or late-onset Alzheimer’s disease (LOAD) is characterized by slowly progressive deterioration and death of CNS neurons. There are currently no substantially disease-modifying therapies. LOAD pathology is closely related to changes with age and include, among others, accumulation of toxic molecules and altered metabolic, microvascular, biochemical and inflammatory processes. In addition, there is growing evidence that cellular energy deficits play a critical role in aging and LOAD pathophysiology. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
21
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(29 citation statements)
references
References 124 publications
(168 reference statements)
8
21
0
Order By: Relevance
“…The pentose phosphate pathway provided NAPDH to fatty acid βoxidation, which then produced acetyl-CoA into the TCA cycle as the energy supply. 47 In the current study, enhanced fatty acid metabolism was shown in the D-gal group, which is consistent with published reports. As reported, the Treg transcription factor Foxp3 could reprogram T cell metabolism by suppressing glycolysis and enhancing oxidative phosphorylation.…”
Section: ■ Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The pentose phosphate pathway provided NAPDH to fatty acid βoxidation, which then produced acetyl-CoA into the TCA cycle as the energy supply. 47 In the current study, enhanced fatty acid metabolism was shown in the D-gal group, which is consistent with published reports. As reported, the Treg transcription factor Foxp3 could reprogram T cell metabolism by suppressing glycolysis and enhancing oxidative phosphorylation.…”
Section: ■ Discussionsupporting
confidence: 93%
“…The increased lactate level in the d -gal + GAA group implied that the energy supply of neurons had been restored by means of lactolysis. The pentose phosphate pathway provided NAPDH to fatty acid β-oxidation, which then produced acetyl-CoA into the TCA cycle as the energy supply . In the current study, enhanced fatty acid metabolism was shown in the d -gal group, which is consistent with published reports.…”
Section: Discussionsupporting
confidence: 93%
“…We previously observed reductions of NAD + and NADH along with other bioenergetic alterations in cells from LOAD patients, including skin fibroblasts and iPSC‐derived NPCs and astrocytes (Ryu, Bormann, et al, 2021; Ryu, Cohen, et al, 2021; Sonntag et al, 2017). Here, we hypothesized that treatment with NR and caffeine might restore NAD levels, and “correct” the bioenergetic profiles of LOAD cells.…”
Section: Introductionmentioning
confidence: 99%
“…PPP leads to reduction of NAPD + to NAPDH, used for fatty acid biosynthesis and regeneration of reduced glutathione. Many brain disorders, including LOAD, show evidence of abnormal bioenergetics, which may lead to diminished neuroprotective capacities, enhancing and accelerating age‐related neuronal decline (Jove et al, 2014; Mattson & Arumugam, 2018; Ryu, Bormann, et al, 2021; Ryu, Cohen, et al, 2021; Sun et al, 2016; Swerdlow & Khan, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation